Central serous chorioretinopathy and antiphospholipid syndrome: Three cases report. (March 2021) - Billoir, Paul; Michon, Adrien; Darnige, Luc
Antiphospholipid syndrome (APS) is an acquired autoimmune disease characterized by recurrent venous or arterial thrombotic events and pregnancy morbidity, with persistently presence of antiphospholipid antibodies (aPL). We report three cases of central serous chorioretinopathy (CSC) associated with APS.